A multilayer plug concept to enhance thickness distribution control of deep thermoformed parts - Duarte, F. M. (2008)
A multilayer plug, consisting of a set of concentric layers with independent movements, is proposed to enhance control of the final thickness distribution of deep thermoformed parts. The concept is validated experimentally and the results are compared with the predictions produced by the T-SIM software package. Given the good approximation between experimental and theoretical data, T-SIM was used to evaluate the influence of several multilayer plug parameters on the final thickness distribution. Changing the relative displacement of the plug layers together with the total plug displacement leads to a range of thickness contours, including profiles with a localised overthickness, or with a smooth thickness variation. The role of the displacement of the outer and inner plug layers is also assessed, showing that the former influences mainly the upper sidewall of the part, whereas the latter determines the thickness of the base.